Graphite negative electrode material and preparation method thereof, secondary battery and electric equipment
By preparing graphite negative electrode materials that meet specific Raman spectral and pore volume curve indexes, and selectively repairing their layered defect structure, the problem of poor fast charging and rate performance of the recovered graphite negative electrode materials is solved, and better kinetics and cycling performance is achieved.
Patent Information
- Application Number
- CN202411795187.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-21
AI Technical Summary
The fast charging and rate performance of existing recycled graphite negative electrode materials is poor.
By preparing a graphite negative electrode material that meets specific Raman spectrum and pore capacity curve indexes, including the intensity ratio A of the D peak in the range of 1340cm-1 to 1400cm-1 and G peak in the range of 1580cm-1 to 1650cm-1, as well as the tangent slope value B at the pore diameter of 50nm in the pore capacity curve, satisfying the relationship formula of 6.1*10-5≤-B/A≤9.55*10-5, the layered defect structure of graphite is selectively repaired to form a material with a lower lithium ion diffusion energy barrier.
The good fast charging performance and rate performance of graphite negative electrode materials are achieved, taking into account both dynamic performance and cycle performance.
Smart Images

Figure CN119674065A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery manufacturing, and in particular to a graphite negative electrode material and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] At present, with the acceleration of the modernization process, the consumption of secondary batteries in the global electronic products, electric vehicles and other industries is increasing, and the recycling and reuse of waste secondary batteries is becoming increasingly important.
[0003] In the existing technology, the recycling of secondary batteries mainly focuses on the recycling of positive electrode active materials such as transition metals such as cobalt, iron, manganese, and positive and negative electrode collectors copper and aluminum. However, the recycling technology and industry for negative electrode graphite are still imperfect, and the fast charging performance and rate performance of the recycled graphite negative electrode material are not good. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a graphite negative electrode material and a preparation method thereof, a secondary battery and an electrical device, so as to solve the problem that the existing recycled graphite negative electrode material has poor fast charging performance and rate performance.
[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:
[0006] The present invention provides a graphite negative electrode material, wherein the graphite negative electrode material satisfies:
[0007] 6.1*10 -5 ≤-B / A≤9.55*10 -5 ; Wherein, A is the graphite negative electrode material in the Raman spectrum curve at 1340cm -1 ~1400cm -1 The D peak and 1580cm -1 ~1650cm -1 The intensity ratio of the G peak in the range;
[0008] B is the tangent slope value at a pore diameter of 50 nm in the pore volume curve of the graphite negative electrode material, and the pore volume curve is measured by a gas adsorption method under a nitrogen atmosphere.
[0009] Furthermore, the graphite negative electrode material also satisfies:
[0010] 1.1≤C / B≤1.6;
[0011] Wherein, C is the tangent slope value at a pore diameter of 100 nm in the pore volume curve of the graphite negative electrode material.
[0012] Furthermore, the specific surface area of the graphite negative electrode material is 0.4m 2 / g~3.6m2 / g.
[0013] Furthermore, the porosity of the graphite negative electrode material is 17% to 45%.
[0014] Furthermore, in the graphite negative electrode material, A satisfies: 0.25<A<0.71.
[0015] Furthermore, the particle size distribution of the graphite negative electrode material satisfies:
[0016] 0.5≤(Dv90-Dv10) / Dv50≤2.2;
[0017] Wherein, Dv10, Dv50, and Dv90 represent the particle sizes corresponding to when the cumulative particle volumes of the graphite negative electrode material reach 10%, 50%, and 90%, respectively.
[0018] Furthermore, the powder compaction density of the graphite negative electrode material under a pressure of 5T is 1.55 g / cm 3 ~2.16g / cm 3 .
[0019] The present invention also provides a method for preparing the above-mentioned graphite negative electrode material, which comprises:
[0020] Disassemble the negative electrode of the used battery with SOC 0%;
[0021] Mechanically crushing the negative electrode sheets of the waste batteries and then sieving them to obtain negative electrode main powder;
[0022] The negative electrode main powder is sintered at a temperature of 1400° C. to 1800° C. and a sintering time of 5 seconds to 300 seconds to prepare a graphite negative electrode material.
[0023] The present invention also provides a secondary battery, which includes a negative electrode plate, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, and the negative electrode active material layer includes the above-mentioned graphite negative electrode material;
[0024] The surface density of the negative electrode active material layer is 80 mg / 1540.25 mm 2 ~160mg / 1540.25mm 2 .
[0025] The present invention further provides an electrical device, which includes the above-mentioned secondary battery, and the secondary battery serves as a power supply for the electrical device.
[0026] Compared with the prior art, the embodiments of the present invention have the following advantages:
[0027] In the embodiment of the present invention, the graphite negative electrode material provided meets the following requirements: 6.1*10 -5 ≤-B / A≤9.55*10 -5 ; Wherein, A is the graphite negative electrode material in the Raman spectrum curve at 1340cm -1 ~1400cm -1 D peak and 1580cm -1 ~1650cm -1 The intensity ratio of the G peak in the range of 1340 cm-1 is 1340 cm-1, and the pore volume curve of the graphite negative electrode material is 1340 cm-1. -1 ~1400cm -1 D peak and 1580cm -1 ~1650cm -1 When the intensity ratio A of the G peak within the range and the tangent slope value B at the pore diameter of 50 nm in the pore volume curve satisfy the above relationship, the layered defect structure of graphite is selectively repaired to form a material with a lower lithium ion diffusion energy barrier, thereby being able to take into account both good fast charging performance and rate performance.
[0028] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the process of preparing the graphite negative electrode material provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] The applicant of the present invention has found that in the prior art, the recycling of secondary batteries mainly focuses on the recycling of positive electrode active materials such as transition metals such as cobalt, iron, and manganese, as well as copper and aluminum of positive and negative electrode current collectors, but the recycling technology and industry for negative electrode graphite are still imperfect. In addition, in the few technologies for recycling negative electrode graphite, the fast charging performance and rate performance of the recycled graphite negative electrode material are poor due to unreasonable sintering methods.
[0032] In order to solve the above problems, the embodiment of the present invention provides a graphite negative electrode material, which satisfies:
[0033] 6.1*10 -5 ≤-B / A≤9.55*10 -5 ;
[0034] Wherein, A is the graphite negative electrode material at 1340 cm in the Raman spectrum curve. -1 ~1400cm -1 D peak and 1580cm -1 ~1650cm -1 The intensity ratio of the G peak in the range;
[0035] B is the tangent slope value at a pore diameter of 50 nm in the pore volume curve of the above-mentioned graphite negative electrode material, and the above-mentioned pore volume curve is measured by gas adsorption method under nitrogen atmosphere.
[0036] The above pore volume curve is measured in a nitrogen atmosphere according to the national standard test method. The specific measurement process refers to GB / T21650.2-2008, Determination of pore size distribution and porosity of solid materials by mercury injection and gas adsorption method Part 2: Analysis of mesopores and macropores by gas adsorption method.
[0037] In the embodiment of the present invention, in the Raman spectrum curve of the graphite negative electrode material, 1340 cm -1 ~1400cm -1 D peak and 1580cm -1 ~1650cm -1 When the intensity ratio A of the G peak within the range and the tangent slope value B at the pore size of 50 nm in the pore volume curve satisfy the above relationship, the layered defect structure of graphite is partially selectively repaired, the isotropy is higher and the diffusion coefficient is larger, forming a material with a lower lithium ion diffusion barrier, so that the graphite negative electrode material has good fast charging performance and rate performance. In this embodiment, -B / A can be, for example, 6.10*10 -5 ,7.50*10 -5 、8.00*10 -5 ,8.80*10 -5 ,9.20*10 -5 ,9.55*10 -5 The range value of one or both of them.
[0038] Optionally, in one embodiment, the Raman spectrum curve of the graphite negative electrode material at 1340 cm -1 ~1400cm -1 D peak and 1580cm -1 ~1650cm -1 The intensity ratio A of the G peak within the range satisfies 0.25<A<0.71, so that the structural strength of the above-mentioned graphite negative electrode material is moderate, and can effectively take into account the diffusion capacity, fast charging performance and cycle performance.
[0039] Optionally, in one embodiment, the above graphite negative electrode material further satisfies:
[0040] 1.1≤C / B≤1.6;
[0041] Wherein, C is the tangent slope value at a pore diameter of 100 nm in the pore volume curve of the graphite negative electrode material.
[0042] In this embodiment, the ratio of the tangent slope values at a pore diameter of 100 nm and a pore diameter of 50 nm in the pore volume curve of the graphite negative electrode material is further defined. When the above-mentioned tangent slope value ratio is in the range of 1.1 to 1.6, it can take into account both good kinetic performance and cycle performance, thereby improving its fast charging performance and rate performance.
[0043] Optionally, in one embodiment, the specific surface area of the graphite negative electrode material is 0.4 m 2 / g~3.6m 2 / g, which is convenient for the graphite negative electrode material to contact and react with the electrolyte to ensure its fast charging performance, and can also take into account the structural strength of the whole material, thereby ensuring its cycle performance. Optionally, in some embodiments, the specific surface area of the above-mentioned graphite negative electrode material can be 0.4m 2 / g, 0.5m 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.5m 2 / g, 2m 2 / g, 3m 2 / g, 3.6m 2 / g or both.
[0044] Optionally, in one embodiment, the porosity of the graphite negative electrode material is 17% to 45%, and the porosity refers to the percentage of the volume of the pores inside the material to the total volume of the material. When the porosity of the graphite negative electrode material is in the range of 17% to 45%, it can provide sufficient contact surface to contact and react with the electrolyte to ensure its fast charging performance, while taking into account the overall structural strength of the material, thereby ensuring its cycle performance.
[0045] Optionally, in some embodiments, the porosity of the graphite negative electrode material may be in the range of one or any two of 17%, 18%, 20%, 25%, 30%, 40%, 45%.
[0046] Optionally, in one embodiment, the particle size distribution of the above-mentioned graphite negative electrode material satisfies:
[0047] 0.5≤(Dv90-Dv10) / Dv50≤2.2;
[0048] Among them, Dv10, Dv50, and Dv90 respectively represent the particle sizes corresponding to when the cumulative particle volumes of the above-mentioned graphite negative electrode materials reach 10%, 50%, and 90%.
[0049] In this embodiment, by optimizing the particle size, the particle size distribution of the graphite negative electrode material is limited to satisfy: 0.5≤(Dv90-Dv10) / Dv50≤2.2, which is beneficial to the grading of large and small particles and filling the pores between the particles, which can significantly improve the dynamic performance and also make the conductive network of the electrode sheet tightly constructed, which can effectively improve the energy density and rate performance of the battery.
[0050] Optionally, in some embodiments, in order to further optimize the rate performance, the particle size distribution of the above-mentioned graphite negative electrode material satisfies: 1.0≤(Dv90-Dv10) / Dv50≤2.0.
[0051] Optionally, in some embodiments, in order to further optimize the rate performance, the particle size distribution of the above-mentioned graphite negative electrode material satisfies: 1.4≤(Dv90-Dv10) / Dv50≤1.6.
[0052] Optionally, in a specific embodiment, the particle size distribution of the graphite negative electrode material satisfies: 0.5 μm ≤ Dv1 ≤ 2 μm. This allows the small particles in the graphite negative electrode material system to effectively fill the gaps between the large particles, which helps to increase the compaction density of the pole piece, thereby improving the volume energy density of the battery.
[0053] The particle size distribution of the above graphite negative electrode material satisfies: 1μm≤Dv10≤20μm. This allows the small particles in the graphite negative electrode material system to effectively fill the gaps between large particles, which helps to increase the compaction density of the pole piece, thereby improving the volume energy density of the battery.
[0054] Optionally, in a specific embodiment, the particle size distribution of the graphite negative electrode material satisfies: 4μm≤Dv50≤50μm. The size of Dv50 is within the above range, which can make the graphite negative electrode material have a suitable specific surface area, help increase the utilization rate of the graphite negative electrode material, and thus improve the capacity and energy density of the battery.
[0055] Optionally, in a specific embodiment, the particle size distribution of the graphite negative electrode material satisfies: 13 μm ≤ Dv90 ≤ 70 μm. This makes the larger particles in the graphite negative electrode material system have a moderate particle size, which is conducive to making the negative electrode plate have a suitable porosity and improving the plate wetting performance.
[0056] Optionally, in a specific embodiment, the particle size distribution of the graphite negative electrode material satisfies: 15 μm ≤ Dv99 ≤ 80 μm. This makes the large particle size in the graphite negative electrode material system moderate, which is conducive to making the negative electrode sheet have a suitable porosity and improving the transmission efficiency of lithium ions.
[0057] Optionally, in one embodiment, the powder compaction density of the graphite negative electrode material under a pressure of 5T is 1.55 g / cm 3 ~2.16g / cm 3 , for example, it can be 1.55 g / cm 3 、1.62g / cm 3 , 1.70g / cm 3 , 1.8g / cm 3 , 1.95g / cm 3 , 2.08g / cm 3 , 2.16g / cm 3 The range of one or any two of the above values can not only reduce the internal resistance and polarization loss, thereby extending the cycle life of the battery, but also facilitate the insertion and extraction of lithium ions to ensure the battery kinetic performance. Optionally, in some embodiments, the powder compaction density of the above carbonaceous material at 5T is 1.76-1.98g / cm 3 .
[0058] The present invention also provides a method for preparing a graphite negative electrode material. Figure 1 As shown, it includes steps 101 to 103:
[0059] Step 101: disassemble the negative electrode sheet of the waste battery with SOC 0%.
[0060] In the above step 101, after the used battery is discharged to SOC 0%, the coil is disassembled and then the negative electrode plate is separated; in the present application, the used battery refers to a battery whose cycle capacity decay reaches less than 80% of the initial capacity, and the negative electrode active material of the battery is graphite material.
[0061] Step 102: Mechanically crush the negative electrode sheets of the waste batteries and then sieve them to obtain negative electrode main powder.
[0062] In the above step 102, the negative electrode sheet is crushed in a mechanical crusher, and then the powder is sieved through a 20-200 mesh sieve to filter out large particles of foil metal, thereby obtaining the negative electrode main powder.
[0063] Step 103, sintering the negative electrode main powder, wherein the sintering temperature is 1400° C. to 1800° C., and the sintering time is 5 s to 300 s, to prepare a graphite negative electrode material.
[0064] In the above step 103, the negative electrode main powder recovered from the waste battery cell is sintered at a temperature of 1400°C to 1800°C, which can not only remove the impurities therein, but also partially repair the layered structure in the graphite, so that the obtained negative electrode active material can finally meet the following requirements: 6.1*10 -5 ≤-B / A≤9.55*10 -5 ; Where A is the graphite negative electrode material in the Raman spectrum curve at 1340cm -1 ~1400cm -1 D peak and 1580cm -1 ~1650cm -1 B is the tangent slope value at a pore diameter of 50 nm in the pore volume curve of the graphite negative electrode material, and the pore volume curve is determined by gas adsorption method under nitrogen atmosphere.
[0065] Optionally, after the sintering treatment, the powder is sieved through 200-400 meshes to obtain a graphite negative electrode material.
[0066] Optionally, in some embodiments, the temperature of the sintering treatment can be one of 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, 1700°C, 1800°C or any two of the range values, and the sintering time can be one of 5s, 10s, 30s, 40s, 50s, 60s, 80s, 100s, 200s, 300s or any two of the range values.
[0067] The present invention also provides a secondary battery, which includes a negative electrode plate, the negative electrode plate includes a negative electrode collector and a negative electrode active material layer arranged on the negative electrode collector, and the negative electrode active material layer includes the above-mentioned graphite negative electrode material.
[0068] In the secondary battery provided by the embodiment of the present invention, the negative electrode plate also includes a conductive agent and a binder; optionally, the conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene, and the binder includes a carboxymethyl cellulose-based binder and a resin binder.
[0069] Optionally, in one embodiment, the carboxymethyl cellulose-based binder includes one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose; and / or the resin-based binder includes one or more of styrene rubber, polyacrylic acid, and polyacrylonitrile.
[0070] In some embodiments, the negative electrode sheet is prepared as follows: the components for preparing the negative electrode sheet, such as the negative electrode active material, binder and conductive agent, are dispersed in a solvent such as deionized water to form a negative electrode slurry; the negative electrode slurry is coated on both sides of a negative electrode collector such as copper foil; after baking, rolling, cutting and other processes, the negative electrode sheet can be obtained.
[0071] In some embodiments, the coating area density of the negative electrode active material layer is 80 mg / 1540.25 mm 2 ~160mg / 1540.25mm 2 , which can maintain good dynamic performance and take into account energy density.
[0072] The secondary battery provided by the embodiment of the present invention further includes a positive electrode plate, a separator and an electrolyte.
[0073] The positive electrode plate includes a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer includes a positive active material, and the positive active material includes a lithium ion transition metal oxide. The lithium ion transition metal oxide includes at least one of lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, and lithium iron phosphate. Optionally, in one embodiment, the positive electrode plate further includes a conductive agent, and the conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, hard carbon, carbon fiber, and carbon microspheres.
[0074] In some embodiments, the positive electrode sheet is prepared as follows: the components for preparing the positive electrode sheet, such as the positive electrode active material including the positive electrode material, the binder and the conductive agent are dispersed in a solvent such as N-methylpyrrolidone to form a positive electrode slurry; the positive electrode slurry is coated on a positive electrode collector such as aluminum foil; after drying, rolling, die cutting and other processes, the positive electrode sheet can be obtained.
[0075] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode, and the electrolyte can be liquid, gel or all-solid. In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent, and the electrolyte salt is a lithium salt.
[0076] In practical applications, the negative electrode sheet, the positive electrode sheet and the separator are wound to obtain a core, the core is placed in a shell, and packaged to obtain a dry cell, and the dry cell is baked and then injected, formed, sealed and sorted to obtain the above-mentioned secondary battery.
[0077] The present invention further provides an electric device, which includes the above-mentioned secondary battery, and the secondary battery serves as a power supply for the electric device.
[0078] For the above-mentioned secondary battery embodiments and electrical equipment embodiments, their negative electrode plates include a negative electrode active material layer, and the above-mentioned negative electrode active material layer includes the above-mentioned negative electrode material, and can achieve the same technical effects. In order to avoid repetition, they will not be described here. For relevant matters, please refer to the partial description of the negative electrode material embodiment.
[0079] In order to make the invention purpose, technical scheme and beneficial effect of the present invention clearer, the present invention is further described below in conjunction with embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0080] The present invention is described in detail below by way of examples.
[0081] Test method:
[0082] (1) Lithium deposition test:
[0083] Place the secondary battery at 25°C for 30 minutes, fully charge it at 3C, place it for 30 minutes, fully discharge it at 1C, place it for 10 minutes, and after 10 cycles of charge and discharge, fully charge the secondary battery at 3C again, place it for 10 minutes, and then stop. Disassemble the battery and observe the interface condition of the negative electrode.
[0084] (2) Charging rate performance test:
[0085] At room temperature, the secondary battery with SOC = 0% state of charge was charged to 3.65V at a current density of 0.33C, and the capacity was recorded as C1;
[0086] Then, at room temperature, charge the cell with SOC=0% to 3.65V at a current density of 2C. The capacity at this time is C2, and the recorded capacity is C2.
[0087] The capacity ratio C2 / C1 is calculated as a test indicator of the charging rate performance.
[0088] (3) Cyclic performance test:
[0089] At 25±2℃, the secondary battery was tested for charge and discharge cycles in the range of 2.5-3.65V at a charge and discharge rate of 1C / 1C, and the battery's first-week discharge capacity and the discharge capacity after 1000 cycles were recorded. The capacity retention rate for 1000 cycles was calculated as follows: discharge capacity for 1000 cycles / discharge capacity for the first cycle*100%.
[0090] Example 1
[0091] (1) Preparation of negative electrode sheet:
[0092] a. Preparation of graphite negative electrode material: After the waste battery is discharged to SOC 0%, the coil is disassembled and the negative electrode sheet is separated. The negative electrode active material in the negative electrode sheet is graphite material. The negative electrode sheet is placed in a mechanical crusher for crushing. After crushing, the powder is sieved through an 80-mesh sieve to remove the metal foil particles in the negative electrode sheet. The sieved material is placed in a high-temperature thermal shock device at 1550°C for sintering for 60 seconds. After sintering, the material is sieved through a 300-mesh sieve to recover the graphite negative electrode material;
[0093] b. Preparation of negative electrode sheet: Graphite negative electrode material, conductive agent carbon black, binder styrene butadiene rubber and sodium carboxymethyl cellulose were mixed in a mass ratio of 96:1:1.5:1.5, deionized water was added as solvent, and the negative electrode slurry was obtained by stirring in a vacuum mixer; 130mg / 1540.25mm 2 The negative electrode slurry was evenly coated on both sides of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then rolled to a compacted density of 1.6 g / cm 3 , and then punched out with a die-cutting machine to obtain the negative electrode sheet that can be used for subsequent battery production.
[0094] (2) Preparation of positive electrode sheet
[0095] 95 parts of positive electrode active material LiFePO4, 2.7 parts of conductive agent carbon black, 1.8 parts of binder PVDF and 0.5 parts of carbon nanotubes were dry mixed by weight to obtain a dry mixture, and then 1.5 parts of solvent NMP were added to the dry mixture, and the mixture was stirred under the action of a vacuum stirrer to obtain a positive electrode slurry;
[0096] The positive electrode slurry is coated on the aluminum foil by extrusion coating, dried at high temperature, rolled, and then cut by die cutting to obtain the positive electrode sheet.
[0097] (3) Preparation of electrolyte
[0098] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1:1, and then 1 mol / L LiPF6 is dissolved in the mixed organic solvent, mixed evenly, and an electrolyte is prepared.
[0099] (4) Preparation of lithium-ion secondary batteries
[0100] The prepared positive electrode sheet, negative electrode sheet and polypropylene separator are wound with a winding machine to obtain a winding core, which is then packaged with an aluminum-plastic film. After being baked under vacuum for 48 hours to remove moisture, an electrolyte is injected, and the battery is then formed and divided to obtain a lithium-ion secondary battery.
[0101] Embodiments 2 to 10
[0102] The preparation method is the same as that of Example 1, except that, during the preparation of the graphite negative electrode material, the sintering time and the sintering temperature are adjusted.
[0103] Examples 11 to 14
[0104] The preparation method is the same as that of Example 1, except that the sieve mesh number is adjusted during the preparation of the graphite negative electrode material.
[0105] Embodiments 15 to 18
[0106] The preparation method is the same as that in Example 1, except that, during the preparation of the negative electrode sheet, the coating weight of the negative electrode slurry is adjusted.
[0107] Comparative Examples 1-2
[0108] The difference between Comparative Examples 1-2 and Example 1 is that, during the preparation of the negative electrode, the sintering temperature and time are adjusted.
[0109] The parameters of the active materials in the negative electrode sheets in the embodiments and comparative examples are shown in Table 1.
[0110] Table 1
[0111]
[0112]
[0113]
[0114] Among them, A is the negative electrode material in the Raman spectrum curve at 1340cm -1 ~1400cm -1 D peak and 1580cm -1 ~1650cm -1 The intensity ratio of the G peak in the range; B is the tangent slope value at a pore diameter of 50nm in the pore volume curve of the negative electrode material, and the pore volume curve is measured by gas adsorption method under nitrogen atmosphere; C is the tangent slope value at a pore diameter of 100nm in the pore volume curve of the negative electrode material. "E-5" in Table 1 is a scientific notation, representing "10 to the power of -5".
[0115] The secondary batteries prepared in the embodiments and comparative examples were subjected to lithium deposition test, charge rate performance test and cycle performance test. The test data are shown in Table 2.
[0116] Table 2
[0117]
[0118] Among them, the standards for each lithium precipitation level are as follows:
[0119] Local slight lithium deposition: The lithium deposition area of the fully charged negative electrode is less than 5%;
[0120] Slight lithium deposition: The lithium deposition area of the fully charged negative electrode is 5-15%;
[0121] Moderate lithium deposition: The lithium deposition area of the fully charged negative electrode sheet accounts for 15-35%;
[0122] Severe lithium deposition: The lithium deposition area of the fully charged negative electrode is greater than 35%.
[0123] In summary, the graphite negative electrode material provided in this embodiment satisfies: 6.1*10 -5 ≤-B / A≤9.55*10 -5 ; Wherein, A is the graphite negative electrode material in the Raman spectrum curve at 1340cm -1 ~1400cm -1 D peak and 1580cm -1 ~1650cm -1 The intensity ratio of the G peak in the range of 1340 cm-1 is 1340 cm-1, and the pore volume curve of the graphite negative electrode material is 1340 cm-1. -1 ~1400cm -1 D peak and 1580cm -1 ~1650cm -1 When the intensity ratio A of the G peak within the range and the tangent slope value B at the pore diameter of 50 nm in the pore volume curve satisfy the above relationship, the layered defect structure of graphite is selectively repaired to form a graphite material with a lower lithium ion diffusion energy barrier, thereby being able to take into account both good fast charging performance and rate performance.
[0124] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.
[0125] The above is a detailed introduction to a graphite negative electrode material and a preparation method thereof, a secondary battery and an electrical device provided by the present invention. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for a general technician in this field, according to the idea of the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A graphite negative electrode material, characterized in that: The graphite negative electrode material meets the following requirements: 6.1*10 -5 ≤-B / A≤9.55*10 -5 ; Wherein, A is the graphite negative electrode material at 1340 cm in the Raman spectrum curve. -1 ~1400cm -1 The D peak and 1580cm -1 ~1650cm -1 The intensity ratio of the G peak in the range; B is the tangent slope value at a pore diameter of 50 nm in the pore volume curve of the graphite negative electrode material, and the pore volume curve is measured by a gas adsorption method under a nitrogen atmosphere.
2. The negative electrode material according to claim 1, characterized in that The graphite negative electrode material also meets the following requirements: 1.1≤C / B≤1.6; Wherein, C is the tangent slope value at a pore diameter of 100 nm in the pore volume curve of the graphite negative electrode material.
3. The graphite negative electrode material according to claim 1, characterized in that The specific surface area of the graphite negative electrode material is 0.4 m 2 / g~3.6m 2 / g.
4. The graphite negative electrode material according to claim 1, characterized in that The porosity of the graphite negative electrode material is 17% to 45%.
5. The graphite negative electrode material according to claim 1, characterized in that A satisfies: 0.25<A<0.
71.
6. The graphite negative electrode material according to claim 1, characterized in that The particle size distribution of the graphite negative electrode material satisfies: 0.5≤(Dv90-Dv10) / Dv50≤2.2; Wherein, Dv10, Dv50, and Dv90 represent the particle sizes corresponding to when the cumulative particle volumes of the graphite negative electrode material reach 10%, 50%, and 90%, respectively.
7. The graphite negative electrode material according to claim 1, characterized in that The powder compaction density of the graphite negative electrode material under a pressure of 5T is 1.55 g / cm 3 ~2.16g / cm 3 .
8. A method for preparing the graphite negative electrode material according to any one of claims 1 to 7, characterized in that: The method comprises: Dismantle the negative electrode plates of waste batteries with SOC 0%; the waste batteries refer to batteries whose cycle capacity decays to less than 80% of the initial capacity, and the negative electrode active material of the batteries is graphite material; Mechanically crushing the negative electrode sheets of the waste batteries and then sieving them to obtain negative electrode main powder; The negative electrode main powder is sintered at a temperature of 1400° C. to 1800° C. and a sintering time of 5 seconds to 300 seconds to prepare a graphite negative electrode material.
9. A secondary battery, characterized in that: A negative electrode sheet comprising a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer comprises the graphite negative electrode material according to any one of claims 1 to 7; The surface density of the negative electrode active material layer is 80 mg / 1540.25 mm 2 ~160mg / 1540.25mm 2 .
10. An electrical device, characterized in that: The secondary battery according to claim 9 is included, and the secondary battery is used as a power supply for the electrical device.
Citation Information
Cited By
Lithium ion battery and power utilization device
CN121237855A